Plant Extract Regulating Pectate Lyase Production in Soft Rotting Bacterial Isolates (The Agriculturists, 2016)
Soft-rotting bacteria caused diseases by secreting the plant cell-wall-degrading enzymes mainly pectate lyase (Pel). In this study, a total of 20 bacterial strains were isolated from soft rotted fruits and vegetables. Among them, 11 isolates produced soft rot symptom on potato tubers. All these isolates were partially characterized. When these isolates were tested for their Pel production in different media, the isolate P1 produced significantly higher amount of Pel than other isolates in M63 glycerol minimal medium. Interestingly, the isolate P1 grown on M63 glycerol minimal medium supplementing with 0.4% of polygalacturonic acid (PGA) and M63 glycerol minimal medium plus 0.4% of PGA and 1% of various plant extracts, Pel production was induced in M63 glycerol minimal medium containing 0.4% of PGA and hyper-induced in M63 glycerol minimal medium plus 0.4% of PGA and 1% of various plant extracts. However, Pel synthesis was not hyper-induced in high concentrations of potato extract. Thus, not only plant extracts but also concentrations of plant extract may be important for hyper-induction of Pel.The Agriculturists 2015; 13(2) 81-88